BRAZIL-CHILE INTERNATIONAL MASTER'S PROGRAM IN NURSING: AN UNPRECEDENTED COLLABORATION - Martini, Jussara Gue; Alarcon Bustos, Elide Mariela (My University, 2020)
and the Universidad de Magallanes, (UMAG), Chile, to respond to their corresponding intrinsic social value, aiming, with this action, to achieve a more prepared and more socially cohesive population.In view of the above, in 2015 both Institutions sign a mutual collaboration agreement in order to develop the International Master's Program in Nursing -MINTER, targeted to nurses from the Magallanes and Chilean Antarctica Region, located in the southernmost end of South America.The policies for the internationalization of education have targeted actions towards an increase in the South-South cooperation, which would characterize Horizontal International Cooperation.As a general rule, Initial International Cooperation starts with training professors, MSs, and PhDs abroad, in order for them to establish academic links and relationships with their peers in the production of research projects, in a movement of Advanced International Cooperation. 1 Higher Education Institutions, especially the Post-Graduate programs, enable partnerships and, consequently, the creation and expansion of international networks among different countries, focused on improving the quality of professional training and academic production.Therefore, the internationalization of Post-Graduate Nursing has specifically become a permanent challenge in the sense of promoting, above all, a qualitative expansion of the body of researchers, emphasizing the international mobility of professors and students, good quality scientific production, and the impact on social reality. 2
Keywords: Master plan